The evolution of large gullies in association with long-term rainfall in the Tsitsa River Catchment, Eastern Cape, South Africa - Anderson, Ryan Leigh; le Roux, Jay; Rowntree, Kate (International Soil and Water Conservation Research, 2025)
Large gullies exist as permanent features in the landscape that impact the surrounding environment and communities. The effect of rainfall on long-term gully evolution is still understudied, especially for large gully systems. The extent of the growth of the gullies of four large gullies in the Eastern Cape Province (South Africa) is explored over a 70-year period (1950–2020) in relation to rainfall. The extent of these gullies was mapped by manually digitizing the gully edges using aerial surveys and SPOT images captured during the study period. Daily rainfall depths were assessed to examine intense rainfall and rainfall erosivity values using the modified Fournier index. The results reveal an exponential trend of the evolution of the gully in which two phases of development of the gully occurred, according to the type of erosion processes that occurred. The first phase (1950–2004) was mainly characterised by the linear lengthening of the gully systems. The second phase (2004–2020) is mainly characterised by the initiation and growth of side branches in the gullies, with greater increases in extent. Both phases recorded highly erosive rainfall. It is postulated that gully expansion accelerated in Phase 2 due to land degradation resulting from increased livestock in the area. This study highlights that intense rainfall, while acting as a driver for gully expansion, is influenced by interconnected factors, including vegetation cover removal and topography. The findings of this study have implications for the results of control measures in large gully systems with dispersive soils.